Comparative analysis of brushless DC and switched reluctance motors for optimizing off-grid water pumping - Avinash Kumar; Sanjay Marwaha; Manpreet Singh Manna; Anupma Marwaha; Rajat Kumar; Mohammad Amir; Mohit Bajaj; Ievgen Zaitsev (Scientific Reports)
Abstract Off-grid water pumping systems (OGWPS) have become an increasingly popular area of research in the search for sustainable energy solutions. This paper presents a finite element method (FEM)-based design and analysis of Brushless-DC (BLDC) and Switched Reluctance Motors (SRM) designed for low-power water pumping applications. Utilizing adaptive finite element analysis (FEA), both motors were designed with identical ratings and design parameters to ensure a fair comparison. The design geometries adhere to the NEMA 42 standard. An (n + 1) switch converter topology was implemented to energize SRM phases, while a Cuk converter coupled with a three-phase voltage source inverter (VSI) was used to power the BLDC motor. The study provides a comprehensive comparative analysis of the torque profiles of both motor types under identical operating conditions. The BLDC motor achieved a maximum torque of 11.5 Nm and an efficiency of 91.9%, while the SRM demonstrated a maximum torque of 3.8 Nm and an efficiency of 94.6%. The torque ripple of the BLDC motor was significantly lower (0.73 pu) compared to the SRM (1.19 pu), indicating smoother operation. Simulation results obtained using advanced computational electromagnetic tools highlight the performance efficiencies and potential advantages of each motor type for off-grid water pumping systems. This research investigates the viability of both BLDC and SRM technologies in enhancing the efficiency and reliability of OGWPS, with the BLDC motor showing superior performance in terms of torque and operational smoothness. The simulation results of converter topologies used for respective motors have been further validated using experimentation on respective prototype motors.